1986
DOI: 10.1007/bf00330534
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequences of Bacillus plasmids pUB110dB, pRBH1 and its copy mutants

Abstract: The deletion plasmids, pRBH1 (1.5 MDa, kanamycin resistance, Kmr) and pUB110dB (1.5 MDa, Kmr), were obtained from pTB913 (2.9 MDa, Kmr, isolated from a thermophilic bacillus) and pUB110 (3.0 MDa, Kmr, from Staphylococcus aureus), respectively. All the nucleotide sequences of these deletion plasmids were determined. Replication origin regions of pRBH1 and pUB110dB contained, respectively, 63 base-pair inverted repeat and a large open reading frame, encoding RepB protein (235 amino acid residues). The nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…2), and we have demonstrated that pIM13 and pE5 accumulate single-stranded DNA. We also noted that there was some homology between the pE5 deletion site, a site in pUB110-pC194 cointegrates that is a recombinational hot spot (5), and a sequence on pTB19 (a Bacillus stearothermophilus plasmid) which is at ajunction between regions of homology and nonhomology with pUB110 (13). These potential intraplasmid recombination sites are shown in Fig.…”
Section: Methodsmentioning
confidence: 82%
“…2), and we have demonstrated that pIM13 and pE5 accumulate single-stranded DNA. We also noted that there was some homology between the pE5 deletion site, a site in pUB110-pC194 cointegrates that is a recombinational hot spot (5), and a sequence on pTB19 (a Bacillus stearothermophilus plasmid) which is at ajunction between regions of homology and nonhomology with pUB110 (13). These potential intraplasmid recombination sites are shown in Fig.…”
Section: Methodsmentioning
confidence: 82%
“…V01282) of plasmid pUB110 from S. aureus ( Fig. 1) (20,27). As previously mentioned, a gene that is identical, except for a 1-bp Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The ant(4Ј)-Ia genes (often referred to in the literature as aadD) were cloned from the plasmids of both Staphylococcus aureus and thermophilic bacilli and turned out to be almost identical except for one base pair difference (180,203). Recently, this gene was detected on the large conjugative plasmid from Staphylococcus aureus (20) and as a part of the mec region from methicillin-resistant staphylococci (138,277).…”
Section: Aminoglycoside Nucleotidyltransferasesmentioning
confidence: 99%